The PIBID Geography Practice as a possibility of (re) elaboration of knowledge about the city / A Prática no PIBID de Geografia como possibilidade de (re)elaboração de saberes sobre a cidade - Rafael Urubá da Silva; Daniele da Silva Severo; Luana Araújo da Silva; Claudionor de Oliveira Silva (Universidade Estadual de Alagoas, 2017)
Reflecting the importance of geography allows us to understand how this science is essential for understanding and intervention in social reality. The aim is to discuss pedagogical practices of PIBID fellows Geography subproject: "The City in Geography Teaching". The educational activities had important methodological steps as: advance planning; data collection in books, magazines and internet searches; music, Brazilian artists that address city and "The City" written by the artist from Pernambuco Chico Science, the song "Crime" Edson Gomes; video, produced by scholars demonstrating the development and transformation of the city of Palmares Union over the years The results show that the city of education in geography classes is of utmost importance for the development of students' criticality in relation to the urban space to which they are inserted, this is important seminars in order to arouse interest in the dynamic process city. Thus it is concluded that the practice of the seminar addressing content for the daily lives of students linked to a global scale develops an interrelationship between teaching and learning both involved in the process.